Analisis Yuridis Pembatalan Putusan Arbitrase di Pengadilan - Husni Kurniawati; Salma Nur Hanifah (University Of Bengkulu Law Journal, 2024)
The arbitration award results in a final and binding decision. However, an annulment attempt can be made based on Article 70 of the ADR Law which is directed at the District Court. This is contrary to the principle of non-intervention of the court in Articles 3 and 11 of the ADR Law. The urgency of this study is to determine the authority of the court and the use of the provisions of Article 70 in the annulment of an arbitration award after the issuance of the Constitutional Court Decision Number 15/PUU-XIII/2015 and Supreme Court Regulation number 3 of 2023. This study uses a normative legal approach with analytical descriptive research specifications. The sources and types of data used are secondary data collected through literature which are analyzed descriptively qualitatively. The results of the study indicate that the District Court only has the authority to cancel based on the elements of Article 70 of the ADR Law without being accompanied by an act of trying it itself. The use of the provisions of Article 70 of the ADR Law still has different opinions even though the Constitutional Court has issued a decision Number 15/PUU-XIII/2015, as in the Semarang District Court Decision No. 01/Arbitrase/2016/PN.Smg and the Supreme Court Decision No. 480B/Pdt-Sus-Arb/2017. The follow-up to the Constitutional Court decision was then made by Supreme Court Regulation number 3 of 2023 to regulate further. However, the regulation still does not clearly regulate the use of the provisions of Article 70 of the ADR Law which contains criminal elements but is carried out in a civil manner. The ambiguity in terms of evidence related to the norms contained in Article 70 will potentially cause legal uncertainty for justice seekers.